Design of Bisma Character as a Supporting Media for the Promotion of Milk Products - Widyasari; Sri Wulandari; Samuel Rihi Hadi Utomo; Sharah Shabina; Brilliant Firdaus Ramadhani (Future Science, 2022)
Character design is closely related to animation. Currently animation is not only popular among children, but also popular among teenagers to adults. Besides having a function as entertainment, animation can also be a medium for education and promotion. This research is a design-based research with the object of research, namely a local Indonesian dairy product called Milkaya. Milkaya is a trademark of CV. Milknesia Nusantara. This research uses descriptive qualitative method. The results of this study are the design of the character design of the Bisma figure who is the main character who will promote Milkaya implant products and educate children about the importance of drinking milk for health.